Identifying PCP and four PCP analogs using the gold chloride microcrystalline test followed by raman microspectroscopy and chemometrics. (February 2020) - Quinn, Matthew; Brettell, Thomas; Joshi, Monica; Bonetti, Jennifer; Quarino, Lawrence
Graphical abstract: Highlights: Gold chloride produces characteristic microcrystals with PCP and four PCP analogs. Spectra can be obtained from PCP and analog microcrystals using a Raman microscope. Chemometrics can be used on Raman shifts to differentiate PCP and four analogs. The method described meets SWGDRUG guidelines for drug identification. Abstract: Identifying drug analogs can be a vexing problem for forensic scientists particularly in today's evolving drug market. This study proposes a method that utilizes microcrystalline tests, Raman microspectroscopy, and chemometrics to help solve this problem. In the present case, the method described was used to clearly differentiate and identify phencyclidine (PCP) and four of its analogs, namely tenocyclidine (TCP), rolicyclidine (PCPy), 3-methoxy phencyclidine (3-MeO PCP), and 4-methoxy phencyclidine (4-MeO PCP). Microcrystals were grown from each drug with gold chloride and examined using polarized light microscopy. Morphological and optical properties such as shape, habit, time of growth, color, retardation colors, type/angle of extinction, and sign of elongation were observed and documented to characterize each microcrystal. Analysis with a Raman microscope was able to provide structural information on the microcrystals. Objective analysis of the microcrystal spectra was done by employing chemometrics. A training set of Raman shifts was compiled and transformed with principal component analysis (PCA) followed by linear discriminant analysis (LDA). The training set was validated by leave-one-out cross validation (LOOCV) and subsequently ran against a separately-compiled test set. Mahalanobis distances between test samples and the clusters of training samples in LDA space were calculated to empirically demonstrate the applicability of this drug analysis technique. From the results of this study, a drug analysis protocol was developed for analysts to use for the identification of PCP, TCP, PCPy, 3-MeO PCP, and 4-MeO PCP and to serve as a model for drug analogs in general.